Diseño de un sistema de costos por procesos para la empresa textil Ardutex dedicada a la elaboración de hilos ubicada en el sector sur del Distrito Metropolitano de Quito - García Chimbo, María Cristina (2015)
Actually companies seek ways to plan and control production costs that enable them to minimize and to have a report on the use of its resources. Since it was not a feasible tool for the case, the information is not relevant to make timely decisions on costs incurred by each production department. The proposed solution is to design a costing system processes that allow you to have information on the allocation of costs, availability of units produced or processed, the status of the equivalent production, the calculation of total costs, the sale price. Companies can identify the cost elements that are directly related to production and those who are not, have information about the inputs and outputs of inventories, payroll out of the workforce, have knowledge of indirect costs, allocation of the cost function; units produced, space in square meters, asset depreciation, cost system consisting of processes; analysis of the physical flow of production units, equivalent calculation for each element of cost of production, determination of total costs for each element of cost of production, calculation of cost per equivalent unit, allocation of the total reserves of production units for units completed and the final balance, accounting registration of economic movements and the state of production and selling costs.